Water Resources Allocation Policy and Socioeconomic Issues in Cyprus - Koundouri, Phoebe; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book does not only aim to present and analyze the Cyprus experience in water resources management, using both local and world experts in the field. It also opts to communicate this experience to other countries that can inform, develop and improve their water resources policies by understanding the strong and weak elements of the Cyprus experience. The dilemma facing Cyprus$1 (Bthat of limited water supplies (both in terms of quantity and quality) in the face of steadily increasing water demand, coupled with a fragmented institutional structure of the water sector$1 (Bis characteristic of most arid and semi-arid countries all over the world. Another common characteristic of Cyprus is that the water management administrative boundaries there do not coincide with the hydrological ones, while the ongoing political problem of the island creates significant administration problems. Finally, Cyprus$1 (Bs way towards implementing the EU WFD can be instructive for newly-accessing EU countries.s
Dedication -- Acknowledgments -- List of Contributors -- 1. Introduction -- 2. Water Resources in Cyprus: Endowments and Water Management Practices -- 3. Water Use Patterns in Cyprus and Demand Management: Towards Water Resources Sustainability -- 4. The Implementation of the European Union Water Framework Directive in Cyprus -- 5. Water Management: Administration and Legislation -- 6. Water Policy Networks: A New Form of Governance for Cyprus? The Case for Nicosia -- 7. The Economics of Water Resource Allocation: Valuation Methods and Policy Implications -- 8. Integrated Water Resources Planning in Cyprus -- 9. Water Pricing Policy in Cyprus: The Implications of the Water Framework Directive -- 10 Water Resources Management and Wetland Conservation: The Case of Akrotiri Wetland in Cyprus -- 11. Facing the Future: Concluding Remarks -- Index.
Keywords: Economics; Science (General).; Engineering design; Environmental sciences; Migration; Economics/Management Science; Economics/Management Science, general; Water Policy/Water Governance/Water Management; Environment, general; Migration; Engineering Design; Science, general